The Quest for a Primary EPSAS Purpose – Insights from Literature and Conceptual Frameworks. (4th May 2019) - Mann, Bianca; Lorson, Peter C.; Oulasvirta, Lasse; Haustein, Ellen
Abstract: Since 2013, the European Union has aimed to harmonize the public sector accounting (PSA) of its member states by developing European Public Sector Accounting Standards (EPSAS). As a prerequisite for consistent EPSAS, a conceptual framework (CF) is to be developed which includes an explicit selection of purposes. Providing an international comparative view with the theoretical underpinning of Nobes' classification, this paper presents a literature-based systematization of PSA purposes. Our systematization is applied to three CFs: one international (IPSAS) and two national (from the USA and Germany, respectively). Through a normative discussion, we conclude that accountability is preferable as the overall accounting purpose. This theoretical lens is used to evaluate the recent status quo of the ongoing EPSAS CF project. This paper thereby develops relevant implications for accounting theory and offers a starting point for standard setters and scholars to prioritize purposes for PSA with respect to different legal frameworks.